Synthesis and characterization of novel bis(thiosemicarbazone) complexes and investigation of their acetylcholinesterase and glutathione S-transferase activities with in silico and in vitro studies - Donmez, Melike; Sekerci, Memet; Adiguzel, Ragip; Oguz, Ercan; Turkan, Fikret; Yildiko, Umit; Colak, Naki (Springer, 2025)
In this study, firstly, bis(thiosemicarbazone) ligand [L: 2,2 '-(2-(2-(4-methoxyphenyl)hydrazineylidene)cyclohexane-1,3-diylidene)bis(hydrazine-1-carbothioamide)] was synthesized by the condensation reaction of thiosemicarbazide and ketone compound (2-(2-(4-methoxyphenyl)hydrazone)cyclohexane-1,3-dione). The metal complexes were synthesized by the reaction of obtained ligand (L) with CuCl22H(2)O, NiCl26H(2)O, CoCl26H(2)O, and MnCl24H(2)O salts. The structures of synthesized ligand and their complexes were characterized using elemental analysis, IR, UV-Vis, H-1-NMR spectra, C-13-NMR spectra, magnetic susceptibility, mass spectra (LC-MS), thermogravimetry analysis-differential thermal analysis (TGA-DTA), and differential scanning calorimetry techniques. According to the results of the analysis, square plane geometry was suggested for Cu and Co complexes. However, the structures of Ni and Mn complexes were in agreement with octahedral geometry. Molecular docking analysis and pharmacological potential of the compound were evaluated to determine the inhibitory potential against acetylcholinesterase (AChE) and Glutathione-S-transferases (GST) enzymes. The compound exhibited strong binding/docking indices of - 5.708 and - 5.928 kcal/mol for the respective receptors. In addition, L-Ni(II) complex was found to be the most effective inhibitor for AChE enzyme with a K-i value of 0.519. However, with a K-i value of 1.119, L-Cu(II) complex was also found to be an effective inhibitor for the GST enzyme.
Keywords: Bis(thiosemicarbazone) ligands; Metal complexes; Enzyme inhibition; Molecular docking